Sugar Consumption and Changes in Dental Caries from Childhood to Adolescence. (April 2016) - Peres, M.A.; Sheiham, A.; Liu, P.; Demarco, F.F.; Silva, A.E.R.; Assunção, M.C.; Menezes, A.M.; Barros, F.C.; Peres, K.G.
There are no prospective studies investigating the effects of sugar-related feeding practices on changes in dental caries from early childhood to young adulthood. The aim of this study was to assess whether sugar-related feeding practices affect dental caries between the ages of 6 and 18 y. This birth cohort study was initiated in 1993 in Pelotas, Brazil. There were 3 dental clinical assessments; at ages 6 y ( n = 359), 12 y ( n = 339), and 18 y ( n = 307). Sugar-related feeding practices were assessed at ages 4, 15, and 18 y. Covariates included sex and life course variables, such as family income, breast-feeding, mother's education, regularity of dental visit, and child's toothbrushing habits. Group-based trajectory analysis was performed to characterize trajectories of time-varying independent variables that had at least 3 time points. We fitted a generalized linear mixed model assuming negative binomial distribution with log link function on 3-time repeated dental caries assessments. One in 5 participants was classified as "high" sugar consumers, and nearly 40% were "upward consumers." "Low consumers" accounted for >40% of the sample. High and upward sugar consumers had higher dental caries prevalence and mean DMFT in all cohort waves when compared with low sugar consumers. Caries occurred at a relatively constant rate over the period of study, but in all sugar consumption groups, the increment of dental caries was slightly higher between ages 6 and 12 y than between 12 and 18 y. Adjusted analysis showed that dental caries increment ratio between ages 6 and 18 y was 20% and 66% higher in upward and high sugar consumer groups as compared with low consumers. The higher the sugar consumption along the life course, the higher the dental caries increment. Even the low level of sugar consumption was related to dental caries, despite the use of fluoride.